The ghrelin-obestatin system in health and disease - I V TereShchenko; P E Kaiushev (Терапевтический архив, 2014)
The role of the ghrelin-obestatin system in health and disease is multifaceted and new ample evidence has been recently accumulated. Ghrelin was discovered much earlier than obestatin so the biological, physiological and pathophysiological, pharmacological aspects of its activity could be studied far better than obestatin. There is no question that these hormones are not antagonists and they are a uniform system. However, there is a need for further studies of the role of this system in the body's vital functions in health and disease. The paper analyzes the accumulated information on the ghrelin-obestatin system in health and disease, assesses the possibility of their use in clinical practice, and pays attention to the unsolved problems to be explored and solved.